Endovascular Treatment of 300 Consecutive Middle Cerebral Artery Aneurysms: Clinical and Radiologic Outcomes - Mortimer, A.M.; Bradley, M.D.; Mews, P.; Molyneux, A.J.; Renowden, S.A. (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: There is controversy as to the best mode of treating MCA aneurysms. We report the results of a large endovascular series of patients treated at our center. MATERIALS AND METHODS: This study was a retrospective analysis of a prospectively acquired data base. All patients with saccular MCA aneurysms treated between November 1996 and June 2012 were included. World Federation of Neurosurgical Societies grade, aneurysm site, size, and aneurysm neck size were recorded, along with clinical outcome assessed with the Glasgow Outcome Scale and radiographic occlusion assessed with the Raymond classification at 6 months and 2.5 years. RESULTS: A total of 295 patients with 300 MCA aneurysms were treated including 244 ruptured aneurysms (80.7%). The technical failure rate was 4.3% (13 patients). Complete occlusion or neck remnant was achieved in 264 (91.4%). Complications included rupture in 15 patients (5%), thromboembolism in 17 patients (5.7%), and early rebleeding in 3 patients (1%). Overall permanent procedural-related morbidity and mortality were seen in 12 patients (7.8%). Of the ruptured aneurysms, 189 (79.4%) had a favorable clinical outcome (Glasgow Outcome Scale score, 4–5). A total of 33 patients (13.6%) died. On initial angiographic follow-up, aneurysm remnant was seen in 18 aneurysms (8.1%). A total of 13 patients (4.3%) were re-treated. CONCLUSIONS: Our experience demonstrates that endovascular treatment of MCA aneurysms has an acceptable safety profile with low rates of technical failure and re-treatment. Therefore, coiling is acceptable as the primary treatment of MCA aneurysms. EVCendovascular coilingGOSGlasgow Outcome ScaleISATInternational Subarachnoid Aneurysm TrialWFNSWorld Federation of Neurosurgical Societies